PELATIHAN PIJAT LAKTASI PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS UPT SUKARAMAI KECAMATAN TAPUNG HULU - Endang Mayasari; Erma Kasumayanti (Universitas Pahlawan Tuanku Tambusai, 2022)
One of the reasons for the failure of breastfeeding is that the mother lacks confidence that her breast milk can meet the nutritional needs of her baby. This happens because the milk does not come out or only comes out a little in the first days after giving birth. The implementation method for this community service program is systematically arranged: a. Preparation stage, b. Preparation of educational materials and promotion of baby massage. c, Activity Implementation Phase, d. Devotion Article Creation, e Evaluation Phase, f. Report Generation Stage Keywords: Lactation massage